Smoking, immunity, and cardiovascular prognosis: a study of plasma IgE concentration in patients with acute myocardial infarction - Zhang, Lili; Zhu, Yanrong; Meng, Xin; Zhang, Yifan; Ren, Qian; Huang, Dong; Chen, Zhong (Frontiers in Cardiovascular Medicine, 2023)
Background Immunoglobulin E (IgE) is implicated in the pathogenesis of acute myocardial infarction (AMI), and smokers often exhibit elevated plasma IgE levels. However, it remains uncertain whether the role of smoking in the development and prognosis of AMI is influenced by IgE levels. This study aimed to investigate the potential contribution of IgE in mediating the association between smoking and AMI. Methods We conducted a prospective study involving 348 consecutive patients with chest discomfort who underwent coronary angiography. Plasma cotinine, an alkaloid present in tobacco, and IgE levels were measured. The patients were followed up for mean 39-months to assess their long-term prognosis based on major adverse cardiac and cerebrovascular events (MACCE). Results Our findings indicate that patients with AMI had higher plasma levels of cotinine and IgE. Univariate analyses demonstrated a positive association between plasma cotinine (OR = 1.7, 95% CI: 1.27–2.26, P < 0.001) and IgE (OR = 2.8, 95% CI: 1.75–4.39, P < 0.001) with AMI. Receiver operating characteristics analyses showed that the combined use of cotinine and IgE (AUC: 0.677) had a larger predictive performance compared to cotinine alone (AUC: 0.639) or IgE alone (AUC: 0.657), although the improvement did not reach statistical significance. Multivariable logistic regression revealed a positive association between plasma cotinine and AMI (OR = 1.70, 95% CI: 1.04–2.78, P = 0.036). Furthermore, the inclusion of plasma IgE in the regression model led to a decrease in the OR and 95% CI of plasma cotinine (OR = 1.66, 95% CI: 1.01–2.73, P = 0.048). Process mediation analyses showed a significant indirect effect of plasma cotinine on AMI mediated through increased plasma IgE. Kaplan–Meier analysis during a mean 39-months follow-up revealed that higher plasma levels of IgE were associated with an increased risk of MACCE following AMI (P = 0.047). However, in the context of the COX regression analysis, no significant correlation was observed between IgE, cotinine and AMI. Conclusion Cotinine exhibits a positive association with AMI, wherein IgE plays a mediating role. Elevated plasma levels of IgE was positively associated with AMI and poor prognosis, which further confirms the adverse role of smoking on the incidence of AMI and prognosis. (Clinical trial registration: ChiCTR2100053000).